The Football Association medical research programme: an audit of injuries in academy youth football - Price, R (BMJ Group, 2004)
Objectives: To undertake a prospective epidemiological study of the injuries sustained in English youth academy football over two competitive seasons. Methods: Player injuries were annotated by medical staff at 38 English football club youth academies. A specific injury audit questionnaire was used together with a weekly return form that documented each club's current injury status. Results: A total of 3805 injuries were reported over two complete seasons (June to May) with an average injury rate of 0.40 per player per season. The mean (SD) number of days absent for each injury was 21.9 (33.63), with an average of 2.31 (3.66) games missed per injury. The total amount of time absent through injury equated to about 6% of the player's development time. Players in the higher age groups (17–19 years) were more likely to receive an injury than those in the younger age groups (9–16 years). Injury incidence varied throughout the season, with training injuries peaking in January (p<0.05) and competition injuries peaking in October (p<0.05). Competition injuries accounted for 50.4% of the total, with 36% of these occurring in the last third of each half. Strains (31%) and sprains (20%) were the main injury types, predominantly affecting the lower limb, with a similar proportion of injuries affecting the thigh (19%), ankle (19%), and knee (18%). Growth related conditions, including Sever's disease and Osgood-Schlatter's disease, accounted for 5% of total injuries, peaking in the under 13 age group for Osgood-Schlatter's disease and the under 11 age group for Sever's disease. The rate of re-injury of exactly the same anatomical structure was 3%. Conclusions: Footballers are at high risk of injury and there is a need to investigate ways of reducing this risk. Injury incidence at academy level is approximately half that of the professional game. Academy players probably have much less exposure to injury than their full time counterparts. Areas that warrant further attention include the link between musculoskeletal development and the onset of youth related conditions such as Sever's disease and Osgood-Schlatter's disease, the significant number of non-contact injuries that occur in academy football, and the increased rates of injury during preseason training and after the mid season break. This study has highlighted the nature and severity of injuries that occur at academy level, and the third part of the audit process now needs to be undertaken: the implementation of strategies to reduce the number of injuries encountered at this level.